Participação dos quimioterápicos genéricos no mercado de saúde suplementar brasileiro: caso autogestão - Campos, Vilma Suely Lopes [UNIFESP] (2009)
Objective: To quantify the market share of the generic chemotherapeutic drugs in a Self-Managed Healthcare Plan Service. Methods: Manual survey of featured bills charging the chemotherapeutic treatments applied to the participants of “CASSI – Caixa de Assistência de Funcionários do Banco do Brasil”;/Assistance relief of the Banco do Brasil employees;/in the states of São Paulo e Rio de Janeiro in the period of July/2004 to February/2005 inclusively, totalizing 228.555 beneficiaries and involving a web of 12.912 service providers, who only 90 had agreements to services focused on oncology, included chemotherapy. Result: From the 1.177.050 featured bills, only 81.097 derived from the service providers included in the study, that is, holding agreements to chemotherapeutic treatment. As these service providers weren’t just experts on Oncology, but usually also general hospitals, the number of bills concerning about the chemotherapy services was reduced to 3.401, which constitutes the universe of our study. These payable documents charged 129 distinct medicines in 11.394 registers, for 70 distinct active principles. The market share of the generic chemotherapeutic was rated in 0,53% considering the charged value, and 1.52% considering the quantity of charged medications. The Reference medications occupied the second place in the market share, with regard to quantity, with 35,39% and the Similar medications, in first place, with 63,09% of the charged medications. Conclusion: Despite the availability of the Generic chemotherapeutic drugs, their market share was not expressive on the bills presented by the service providers. We verified the market share of the Generic chemotherapeutic in 1,5% if considering the quantity of medications, and 0,5 if considering the value. It’s important a bigger participation of the Healthcare Plan Service on the responsible decision about the indicated treatment, as well as the participator’s. In terms, the chaos, which had already been foreseen, aggravates itself, for the resources are also limited to Health.